Fermentation of dried distillers grains with solubles: scalability and physical properties analysis - Wilson, Jonathan (Kansas State University, 2015)
Whole stillage and thin stillage from the ethanol production process were evaluated as substrate sources for the production of [beta]-carotenes using Sporobolomyces Roseus (ATCC 28988). This product has the potential to be used as a novel feed ingredient for poultry, swine, or cattle diets. [Beta]-carotenes have been supplemented in animal diets to improve animal health, enhance meat color and quality and increase vitamin A concentrations in milk and meat. Microbial fermentations involving growth and product kinetics were performed in 500 mL baffled shake flasks and in a 5 L fermentation bioreactor. Media optimization was conducted in shake flasks to evaluate two carbon sources: glucose and glycerol, and two nitrogen sources: ammonium sulfate and urea. Final [beta]-carotene concentration of 272.57±4.34 [mu]g [beta]-carotene/g biomass was found to be highest for the whole stillage, with 10 g/L added glucose and 10 g/L nitrogen added through ammonium sulfate supplementation. Glycerol addition yielded no significant increase (P<.05) in [beta]-carotene yield, while urea addition significantly decreased (P<.05) the final [beta]-carotene concentrations. The resulting fermented product can be blended with regular feed using either whole stillage as a dry feed ingredient or thin stillage as a liquid feed additive. The fermentation of whole stillage significantly influenced the physical and flow properties of the material. Even though there was a significant decrease (P<0.05) in bulk density and increase (P<0.05) in tapped density between DDGS and fermented whole stillage, there was a less pronounced difference between the whole stillage and fermented whole stillage. The fermentation of whole stillage significantly influenced the physical and flow properties of the material. This showed that the fermentation process and resulting nutritional profile had a significant effect on the resulting fermented whole stillage. A 50 L bioreactor was specifically designed to evaluate the scalability of the process and to perform subsequent feed production trails. Pilot scale feed pelleting runs were conducted and the resultant product was put in environmental chambers to determine if [beta]-carotene concentration was reduced as a result of storage. There was a significant decrease (P<0.05) in [beta]-carotene levels after pelleting and after 28 d of storage at elevated temperature and humidity. These decreases were consistent with previous research.
Keywords: Fermentation; Bioprocessing; Feed Ingredients; Physical Properties; DDGS; Animal Sciences (0475)